2022
DOI: 10.1097/qai.0000000000002904
|View full text |Cite
|
Sign up to set email alerts
|

The Organization, Content, and Case-Finding Effectiveness of HIV Assisted Partner Services in High HIV Morbidity Areas of the United States

Abstract: Background:The contemporary effectiveness of assisted partner notification services (APS) in the United States is uncertain.Setting:State and local jurisdictions in the United States that reported ≥300 new HIV diagnoses in 2018 and were participating in the Ending the Epidemic Initiative.Methods:The study surveyed health departments to collect data on the content and organization of APS and aggregate data on APS outcomes for 2019. Analyses defined contact and case-finding indices (i.e., sex partners named and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…16,19 HIV PN effectiveness also appears to have declined over time in both the US and UK. [19][20][21][22][23] Overall, these studies suggest that provider or conditional referral can increase PN and treatment, but the magnitude of that effect is uncertain, and most recent studies suggest the impact of the intervention is small.…”
Section: Traditional Assisted Partner Notificationmentioning
confidence: 99%
“…16,19 HIV PN effectiveness also appears to have declined over time in both the US and UK. [19][20][21][22][23] Overall, these studies suggest that provider or conditional referral can increase PN and treatment, but the magnitude of that effect is uncertain, and most recent studies suggest the impact of the intervention is small.…”
Section: Traditional Assisted Partner Notificationmentioning
confidence: 99%
“…Now, in addition to linking patients to clinic for STI treatment, linkage to HIV PrEP or HIV antiretroviral rapid start initiation is feasible. A recent analysis demonstrated that 88% of surveyed high HIV morbidity state and local jurisdictions endorsed that their HIV APS programs routinely integrated APS with routine linkage to HIV care and HIV PrEP referrals 5 . However, geographic heterogeneity in the role of DIS in linkage to care activities is highly likely, and although it is certain that variation exists, the extent of variation and the predictors of successful integration of HIV prevention activities into the DIS role are not clear and should be the focus of future research.…”
Section: Linkage To Carementioning
confidence: 99%
“…A recent network modeling study found HIV PS to be highly efficient, requiring lower resources per infection averted 10 . Despite the benefits of HIV PS in promoting diagnoses of HIV among those infected, evidence suggests that partner identification through HIV PS in the United States is declining 7 . An important first step in addressing this decline is to identify areas for improvement in HIV PS implementation.…”
mentioning
confidence: 99%
“…A systematic review conducted in 2007 found that 14% to 20% of partners named and tested were newly diagnosed with HIV 6 . A more recent analysis focusing on US counties and states included in the Ending the HIV Epidemic in the U.S. initiative found that 20% of HIV PS partners who were tested in 2019 were newly diagnosed with HIV 7 . Two studies found HIV PS to be cost saving.…”
mentioning
confidence: 99%
See 1 more Smart Citation